Peroxisome-Deficiency and HIF-2α Signaling Are Negative Regulators of Ketohexokinase Expression - Eberhart, Tanja; Schönenberger, Miriam J.; Walter, Katharina M.; Charles, Khanichi N.; Faust, Phyllis L.; Kovacs, Werner J. (Frontiers in Cell and Developmental Biology, 2020)
Ketohexokinase (KHK) is the first and rate-limiting enzyme of fructose metabolism. Expression of the two alternatively spliced KHK isoforms, KHK-A and KHK-C, is tissue-specific and KHK-C is predominantly expressed in liver, kidney and intestine and responsible for the fructose-catabolizing function. While KHK isoform choice has been linked to the development of disorders such as obesity, diabetes, cardiovascular disease and cancer, little is known about the regulation of total KHK expression. In the present study, we investigated how hypoxic signaling influences fructose metabolism in the liver. Hypoxia or von Hippel-Lindau (VHL) tumor suppressor loss leads to the stabilization of hypoxia-inducible factors alpha (HIF-1α and HIF-2α) and the activation of their signaling to mediate adaptive responses. By studying liver-specific Vhl, Vhl/Hif1a, and Vhl/Epas1 knockout mice, we found that KHK expression is suppressed by HIF-2α (encoded by Epas1) but not by HIF-1α signaling on mRNA and protein levels. Reduced KHK levels were accompanied by downregulation of aldolase B (ALDOB) in the livers of Vhl and Vhl/Hif1a knockout mice, further indicating inhibited fructose metabolism. HIF-1α and HIF-2α have both overlapping and distinct target genes but are differentially regulated depending on the cell type and physiologic or pathologic conditions. HIF-2α activation augments peroxisome degradation in mammalian cells by pexophagy and thereby changes lipid composition reminiscent of peroxisomal disorders. We further demonstrated that fructose metabolism is negatively regulated by peroxisome-deficiency in a Pex2 knockout Zellweger mouse model, which lacks functional peroxisomes and is characterized by widespread metabolic dysfunction. Repression of fructolytic genes in Pex2 knockout mice appeared to be independent of PPARα signaling and nutritional status. Interestingly, our results demonstrate that both HIF-2α and peroxisome-deficiency result in downregulation of Khk independent of splicing as both isoforms, Khka as well as Khkc, are significantly downregulated. Hence, our study offers new and unexpected insights into the general regulation of KHK, and therefore fructolysis. We revealed a novel regulatory function of HIF-2α, suggesting that HIF-1α and HIF-2α have tissue-specific opposing roles in the regulation of Khk expression, isoform choice and fructolysis. In addition, we discovered a previously unknown function of peroxisomes in the regulation of fructose metabolism.